Implementation of supervisory control systems based on state machines - Possan Jr. M.C. (2009)
This paper presents a new methodology for the implementation of discrete event-based control systems. An algorithm is proposed to transform an automatabased supervisor obtained from the Supervisory Control Theory (SCT) in a Mealy finite state machine. This machine may be simplified in order to have a reduced number of state transitions. The machine simplification represents a formal method for a discrete event control system to be implemented in a controller. It is presented an example of a manufacturing system to illustrate such procedure. The implementation of the control for this system is performed in Ladder, a useful language for Programmable Logic Controllers (PLCs). The methodology may be expanded to other programming languages and controller types as well. ©2009 IEEE.